Overexpression of SlOFP20 in Tomato Affects Plant Growth, Chlorophyll Accumulation, and Leaf Senescence - Zhou, Shengen; Cheng, Xin; Li, Fenfen; Feng, Panpan; Hu, Gongling; Chen, Guoping; Xie, Qiaoli; Hu, Zongli (Frontiers in Plant Science, 2019)
Previous studies have shown that OVATE family proteins (OFPs) participate in various aspects of plant growth and development. How OFPs affect leaf chlorophyll accumulation and leaf senescence has not been reported yet. Here, we found that overexpression of SlOFP20 in tomato not only impacted plant architecture but also enhanced the leaf chlorophyll accumulation and retarded leaf senescence. Gene expression analysis of SlGLK1, SlGLK2 and HY5, encoding transcription factors that are putatively involved in chloroplast development and chlorophyll levels, were significantly up-regulated in SlOFP20-OE lines. Both chlorophyll biosynthesis and degradation genes were distinctly regulated in transgenic plants. Moreover, SlOFP20-OE plants accumulated more starch and soluble sugar than WT plants, indicating that an increased chlorophyll content conferred some higher photosynthetic performance in SlOFP20-OE plants. Furthermore, The levels of leaf senescence-related indexes, such as hydrogen peroxide (H2O2), malondialdehyde (MDA) and antioxidant enzymes activities, were differently altered, too. SlOFP20 overexpression repressed the expression of senescence-related genes, SAG12, RAV1 and WRKY53. Moreover, ABA and ethylene synthesis genes were down-regulated in transgenic lines. These results provide new insights into how SlOFP20 regulates chlorophyll accumulation and leaf senescence.